Practitioners perceptions of the soccer extra-time period: Implications for future research - Harper, L. D.; Fothergill, M.; West, D. J.; Stevenson, E.; Russel, M. (PLOS ONE, 2016)
Qualitative research investigating soccer practitioners` perceptions can allow researchers to create practical research investigations. The extra-time period of soccer is understudied compared to other areas of soccer research. Using an open-ended online survey containing eleven main and nine sub questions, we gathered the perceptions of extra-time from 46 soccer practitioners, all working for different professional soccer clubs. Questions related to current practices, views on extra-time regulations, and ideas for future research. Using inductive content analysis, the following general dimensions were identified: `importance of extra-time`, `rule changes`, `efficacy of extra-time hydro-nutritional provision`, `nutritional timing`, `future research directions`, `preparatory modulations` and `recovery`. The majority of practitioners (63%) either agreed or strongly agreed that extra-time is an important period for determining success in knockout football match-play. When asked if a fourth substitution should be permitted in extra-time, 67% agreed. The use of hydro-nutritional strategies prior to extra-time was predominately considered important or very important. However; only 41% of practitioners felt that it was the most important time point for the use of nutritional products. A similar number of practitioners account (50%) and do not (50%) account for the potential of extra-time when training and preparing players and 89% of practitioners stated that extra-time influences recovery practices following matches. In the five minute break prior to extra-time, the following practices (in order of priority) were advocated to players: hydration, energy provision, massage, and tactical preparations. Additionally, 87% of practitioners advocate a particular nutritional supplementation strategy prior to extra-time. In order of importance, practitioners see the following as future research areas: nutritional interventions, fatigue responses, acute injury risk, recovery modalities, training paradigms, injury epidemiology, and environmental considerations. This study presents novel insight into the practitioner perceptions of extra-time and provides information to readers about current applied practices and potential future research opportunities.